2016
DOI: 10.3925/jjtc.62.664
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for the in-House Production of Cryoprecipitate

Abstract: 大石 晃嗣 1) 16) 松本 剛史 1) 16) 田中 由美 1) 牧野 茂義 2) 16) 玉木 茂久 3) 16) 森 恵子 3) 藤盛 好啓 4) 16) 池本 純子 4) 岩尾 憲明 5) 16) 加藤 栄史 6) 16) 紀野 修一 7) 16) 竹下 明裕 8) 16) 山田千亜希 8) 藤井 聡 9) 10) 16) 渡辺 直樹 10) 大塚 浩平 10) 山本 晃士 11) 16) 星野 鉱二 12) 宮崎 研一 13) 前田 平生 14) 16) 宮田 茂樹 15) 16) キーワード:クリオプレシピテート,フィブリノゲン,プロトコール

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Standard method: In brief, one pack of CRYO was prepared from a bag of divided FFP (240 ml), and it was thawed at 2–6°C for 18 h. The bag was then centrifuged at 3180 g for 10 min (Large Capacity Refrigerated Centrifuge, Model 8730, KUBOTA, Tokyo, Japan), and the sediment (CRYO) was re‐suspended in 30–40 ml of plasma 1, 10 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard method: In brief, one pack of CRYO was prepared from a bag of divided FFP (240 ml), and it was thawed at 2–6°C for 18 h. The bag was then centrifuged at 3180 g for 10 min (Large Capacity Refrigerated Centrifuge, Model 8730, KUBOTA, Tokyo, Japan), and the sediment (CRYO) was re‐suspended in 30–40 ml of plasma 1, 10 …”
Section: Methodsmentioning
confidence: 99%
“…In this study, we modified a thaw-siphon method for CRYO production from the perspective of fibrinogen recovery and showed that the modified thaw-siphon CRYO preparation, named the B (Bokutoh)-siphon method, is not inferior to the standard method originally used. 1…”
Section: Introductionmentioning
confidence: 99%
“…In this study, cryoprecipitate was produced by our staff from the Department of Transfusion Medicine using a modified method as previously described. 14) In brief, one pack of cryoprecipitate was prepared from type AB RhD-positive FFP (480 mL) by collecting the precipitate formed during controlled thawing at 4°C and re-suspending in 30–50 mL plasma. The cryoprecipitate can be stored up to a year at temperatures of −20°C or lower.…”
Section: Methodsmentioning
confidence: 99%
“…Since CRYO is not supplied by the Japan Red Cross Society, CRYO was pre-Open Journal of Blood Diseases pared and produced by staff of our Department of Transfusion Medicine, using a modified method as previously described [8]. Briefly, one pack of CRYO was prepared from type AB RhD-positive FFP (480 mL) by collecting the precipitate formed during controlled thawing at 4˚C for 24 hours and re-suspending it in 30 -50 mL of plasma.…”
Section: In-house Cryo and Blood Productsmentioning
confidence: 99%
“…However, CRYO is neither produced nor supplied by the Japanese Red Cross Society. In-house CRYO is produced in our hospital using a method described by the Japan Society of Transfusion Medicine and Cell Therapy [8]. Therefore, we aimed to evaluate the feasibility of our transfusion practice of producing in-house CRYO for the patients with severe upper GI bleeding.…”
Section: Introductionmentioning
confidence: 99%